Study of Enteritis Morbidity Among Neonatal Goats in Iraq - A. Nief, Anaam,; S. Eskandar, Senan; S. Shekhoo, Lodia, (Iraqi Journal of Science, 2023)
The study was aimed to investigate the morbidity of enteritis in goate from 2007 to 2011 by using 149 records contained veterinarian and breeding records from birth to yearling age to study factors refer to animals and that in relationship with enteritis morbidity included: breed, year, birth type, sex, birth weight, weaning weight, mother weight, season and age. General mean for enteritis incident rate was 0.94% and this not affected by birth type, sex, weaning weight, maternal weight, while significantly (p<0.05) affected by breed and birth weight and highly significant affect by year, season and age. This study indicated that local goats and shami have incidence rate received to 1.30% and 1.36% while for cross goats (local x Shami) and (Shami x cross) was 0.67% and 0.68% respectively, incidences variance among years the lower was 0.71% for year 2009 while occilated for other years between 1.11% and 1.04% for 2007 and 2011 respectively. According to twin and triplet neonatal their incidence higher than single one and were 1.02%, 1.01% and 0.97% respectively. Male and female equalities in their morbidity. The higher incidence was 1.12% for heaviest neonatal more than 4Kg and reduced for weights between 2-4Kg received to 0.94%, in the other hand neonatal with weaning weight less than 12Kg their lower morbidity percentage was 0.98%, while spread among those with weight more than 20Kg received to 1.03%, but according to mothers with weights lessthan35Kg and more than 50Kg their natal morbidity percentage were 1.01% and 1.02% and reduced to 0.98% for natal due to mother with weights between 35-50Kg. The occurrence of disease variance among different season received to 1.09%, 1.04%, 1.03, 0.86%, in spring, summer, autumn and winter respectively. This study observed that incidence rates for buckling and dueling were 0.58%, 1.33% for pre weaning and 0.67%, 1.45% for post weaning to local and Shami goats respectively. Heritability for incidence rate due to enteritis received to 0.54. Correlation coefficient between enteritis disease and each of breed and birth weight and age 0.213 (p <0.01), 0.060(non significant), 0.227 (p <0.01) respectively, correlation coefficient between breed and each of birth weight and age 0.113 (non significant) and 0.532 (p < 0.01), while correlation coefficient between birth weight and age received to 0.007 (non significant).